Sebacinales are common mycorrhizal associates of Ericaceae - Selosse, Mark André (2007)
Previous reports of sequences of Sebacinales (basal Hymenomycetes) from ericoid mycorrhizas raised the question as to whether Sebacinales are common mycorrhizal associates of Ericaceae, which are usually considered to associate with ascomycetes. Here, we sampled 239 mycorrhizas from 36 ericoid mycorrhizal species across the world (Vaccinioideae and Ericoideae) and 361 mycorrhizas from four species of basal Ericaceae lineages (Arbutoideae and Monotropoideae) that do not form ericoid mycorrhizas, but ectendomycorrhizas. Sebacinales were detected using sebacinoidspecific primers for nuclear 28S ribosomal DNA, and some samples were investigated by transmission electron microscopy (TEM). Diverging Sebacinales sequences were recovered from 76 ericoid mycorrhizas, all belonging to Sebacinales clade B. Indeed, some intracellular hyphal coils had ultrastructural TEM features expected for Sebacinales, and occurred in living cells. Sebacinales belonging to clade A were found on 13 investigated roots of the basal Ericaceae, and TEM revealed typical ectendomycorrhizal structures. Basal Ericaceae lineages thus form ectendomycorrhizas with clade A Sebacinales, a clade that also harbours ectomycorrhizal fungi. This further supports the proposition that Ericaceae ectendomycorrhizas involve ectomycorrhizal fungal taxa. When ericoid mycorrhizas evolved secondarily in Ericaceae, a shift of mycobionts occurred to ascomycetes and clade B Sebacinales, hitherto not described as ericoid mycorrhizal fungi.